2022
DOI: 10.1007/s00894-022-05168-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and thermal and computational investigations of the l-histidine bis(fluoride) crystal

Abstract: Nonlinear optical materials have been investigated recently due to their potential technological applications in information storage and communications. In this context, semi-organic crystals can effectively combine the desired nonlinear optical properties of amino acids with the promising mechanical and thermal properties of inorganic materials. In this work, we have synthesized and characterized a semi-organic crystal of the amino acid l-histidine and hydrofluoric acid and investigated the chemical interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…As shown in the PXRD curves ( Figure 4C ), a great deal of intense peaks ranging from 5° to 35° were observed for Free NOB, indicating the crystalline state of NOB, whereas there was no crystal diffraction peak in the carrier mixture of Soluplus and PVP/PV 64 because of their amorphous nature. 30 , 31 Diffraction peaks with 10°–15° and 20°–25° were still obviously observed in NOB/PM even though their intensities were weaker than those of Free NOB, which indicated the presence of NOB crystals in NOB/PM. However, the weak diffraction peaks (10°–15° and 20°–25°) were disappeared in the NOB/SD formulation, which confirmed that NOB existed an amorphous state in NOB/SD formulation.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in the PXRD curves ( Figure 4C ), a great deal of intense peaks ranging from 5° to 35° were observed for Free NOB, indicating the crystalline state of NOB, whereas there was no crystal diffraction peak in the carrier mixture of Soluplus and PVP/PV 64 because of their amorphous nature. 30 , 31 Diffraction peaks with 10°–15° and 20°–25° were still obviously observed in NOB/PM even though their intensities were weaker than those of Free NOB, which indicated the presence of NOB crystals in NOB/PM. However, the weak diffraction peaks (10°–15° and 20°–25°) were disappeared in the NOB/SD formulation, which confirmed that NOB existed an amorphous state in NOB/SD formulation.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, hydrogen bonds in terms of percentage exhibit a more significant amount in other compounds based on organic molecules such as amino acids and their complexes. 61,62…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, hydrogen bonds in terms of percentage exhibit a more signicant amount in other compounds based on organic molecules such as amino acids and their complexes. 61,62 3.3 Group theory and vibrational properties at temperatures of 300 and 100 K 3.3.1 Group-theory analysis. According to group theory, all fundamental vibrations of AA crystal in the B m form are described through the A g , A u , B g and B u irreducible representations of C 2h -factor group.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…However, B3LYP and other popular functionals are unsuitable for studying systems where noncovalent interactions play a key role. , On the other hand, new DFT-based functionals have been implemented with empirical corrections for dispersion energy duly to ensure greater accuracy in treating long-range interactions. This is the case of the DFT functional ωB97X-D, which is also robust for its use in the study of the thermochemistry of organic systems. , Therefore, a DFT study is performed herein employing the ωB97X-D functional and 6-31G­(d) basis set for the calculations for the individual compounds (RIF and TRIS) and to study interactions in the heterodimer (RIF–TRIS) that constitutes the coamorphous material, contributing to the elucidation of its formation and physical stability. Spectroscopic and thermodynamic data, as well as electronic properties of RIF, TRIS, and the RIF-TRIS heterodimer, were calculated in this work.…”
Section: Introductionmentioning
confidence: 99%